Strategi Penyusunan RPP PAI Berbasis Digital dalam Meningkatkan Efektivitas Kinerja Guru - Farhanah, Ai Nafa; Restu, Yanto Maulana; Syaurah, Alya Lifadllisy; Hilmi, Riza Fu’ad; Jaelani, Jenjen (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the strategy for developing digital-based Islamic Religious Education (PAI) Lesson Plans (RPPs) and their contribution to teacher performance effectiveness. Ideally, lesson plan development should follow systematic principles in accordance with educational regulations. However, research findings indicate that the digitalization of lesson plan development at SMA Negeri 7 Tasikmalaya City is not yet fully optimized. Teachers still rely on Microsoft Word as the primary tool, while digital technologies such as Google, learning apps, and artificial intelligence (AI) are only utilized as aids in searching for references and comparing materials. Conversely, the use of digital technology is more dominant in the learning implementation stage through the use of Canva and Filmora to create audio-visual media that have been proven to improve student understanding and learning interest. Furthermore, digital technology also has a significant impact on teacher work time efficiency, through the school intranet system that is capable of automatic correction and digital grade recapitulation. This study emphasizes the importance of strengthening teachers' digital competencies, institutional support, and developing an innovative work culture so that the digitalization of lesson planning can be implemented optimally and sustainably. Keywords: PAI lesson plan, digital technology, teacher performance effectiveness, instructional planning, learning media